Dual-energy spectral CT in assessment of pleural effusion - Muang-im , Wilailak; Euathrongchit, Juntima; Tantraworasin , Apichat; Wannasopha, Yutthaphan (The ASEAN Journal of Radiology, 2022)
Background: Pleural effusion is a common clinical problem. The ability to differentiate between benign and malignant pleural effusions has many clinical benefits. However, few studies have investigated the diagnostic value of dual-energy spectral computed tomography (DECT) in pleural effusion. Objective: To evaluate the diagnostic values of DECT for assessment of pleural effusion. Materials and Methods: We retrospectively analyzed data from 87 patients presenting with pleural effusion who underwent chest DECT from October 2019 to November 2020. Two reviewers blindly reviewed the CT images of pleural effusion in consensus. The pleural fluid attenuation in standard conventional CT images and monoenergetic images, at 40 keV, 100 keV and 140 keV, were recorded. Data pertaining to the effective atomic number, the iodine concentration (IC)and associated CT findings including pleural thickening, pleural nodules and extrapleural fat clouding was analyzed. Results: Of 87 patients, 44 were presented with benign effusions and the remaining 43 were presented with malignancy.There were no statistically significant differences in differentiating between benign and malignant pleural effusions by using the attenuation values, the effective atomic number or the IC. Irregular pleural thickening and pleural nodules were detected statistically significant in the patients with malignant pleural effusions with moderate accuracy, (48.83%; p < 0.01; AuROC 0.7103 and 34.88%; p < 0.01; AuROC 0.654 respectively). Conclusion: DECT attenuation values did not show any reliable clinical value in the differentiation between benign and malignant pleural effusions. The presence of pleural nodules or irregular pleural thickening would suggest malignant pleural effusion with moderate accuracy.